Using community/researcher partnerships to develop a culturally relevant intervention for children with communication disabilities in Kenya. - Hartley, S; Murira, G; Mwangoma, M; Carter, J; Newton, C (2009)
PURPOSE: The objective of this study is to develop a culturally relevant community-based intervention for children with communication disabilities in Kenya through a community/researcher partnership. The resulting intervention is for use in a randomized control trial which will be reported at a later stage. METHOD: Using a qualitative approach, initial data was collected through focus group discussions with women, disabled people and traditional dancers. The groups examined the needs, problems and challenges faced by disabled children and their families. This generated the content and structure for a series of participatory workshops with a further two women's groups. These workshops strove to generate a culturally relevant community-based intervention programme for children with communication disabilities and their families. The content and balance of the resulting intervention was observed to be different from existing programmes described in the literature. Notably it included many culturally appropriate strategies for increasing social integration and raising community awareness. RESULTS: The process of generating a locally relevant community-based rehabilitation intervention is potentially transferable and has particular relevance to the estimated 80% of the world where there are no formal rehabilitation services for children with disabilities and where women's groups are a strong element of local culture. CONCLUSION: (i) Community/researcher partnerships can be used to develop interventions; (ii) such interventions are different from those imported from other cultures; and (iii) this process is transferable and can be part of the preparations for a Randomized Control Trial.